Implementation of Teaching KetamansiswaanTri-N to Instil Noble Characteristics of Students at SDN I Plumbon, Karanganyar District (JED (Jurnal Etika Demokrasi), 2020)
The purpose of this study was to determine the process of implementing Tri-N Student Teachings Ketamansiswaan Tri-N to Instil Noble Characteristics of SD N 1 Plumbon Students in Karanganyar Subdistrict, the obstacles encountered in implementing Tri-N Student Teachings to instil noble character of SD NI Plumbon students and to find solutions used to overcome obstacles in the implementation of Tri-N Student Teachings to instil the noble character of students of Plumbon Elementary School NI Karanganyar. This type of research is a type of qualitative research. The data used in this study are primary data, the data obtained directly from research subjects. The instrument of this study was the researcher himself, assisted by interview guidelines, questionnaires, observations and documentation. Methods of data analysis by data reduction, data presentation, drawing conclusions and verification as well as checking the validity of the data with triangulation techniques. The targeted output of this study is an accredited national journal. The results of the data analysis can be concluded that by using the right learning model, it can provide maximum learning outcomes. Learning model with the concept of 3N (Niteni, Nirokke, Nambahi) can be applied in Civics learning. By applying this 3N concept, students are expected to be able to carry out learning to the maximum that is observing learning objects, then imitating what students have observed, and the final stage of students can improve by adding to the learning object so that in teaching and learning process, students will produce knowledge and skills.Keywords:Implementasion,learning Ketamansiswaan Tri-N,Noble Character Tujuan penelitian ini adalah untuk mengetahui proses pengimplementasian Ajaran Ketamansiswaan Tri-N untuk Menanamkan Budi Pekerti Luhur Siswa SD N  1 Plumbon Kecamatan Karanganyar, kendala yg dihadapi dalam pengimplementasian Ajaran Ketamansiswaan Tri-N unuk menanamkan budi pekerti luhur siswa SD N I Plumbon dan untuk mengetahui solusi yang digunakan untuk mengatasi kendala dalam  pengimplementasian Ajaran Ketamansiswaan Tri-N untuk menanamkan budi pekerti luhur siswa SD N I Plumbon Kecamatan Karanganyar. Jenis penelitian ini adalah jenis penelitian kualitatif. Data yang digunakan dalam penelitian ini adalah data primer, yaitu data yang diperoleh langsung dari subjek penelitian. Instrumen dalam penelitian ini adalah peneliti sendiri dengan dibantu pedoman wawancara, angket, observasi dan dokumentasi. Metode analisis data dengan reduksi data, penyajian data, penarikan simpulan dan verifikasi serta pengecekan keabsahan data dengan teknik triangulasi. Luaran yang ditargetkan dalam penelitian ini adalah jurnal nasional terakreditasi. Hasil analisis data dapat disimpulkan bahwa menggunakan model pembelajaran yang tepat dapat memberikan hasil pembelajaran yang maksimal. Model pembelajaran dengan konsep 3N (Niteni, Nirokke, Nambahi) dapat diterapkan dalam pembelajaran PKn. Dengan menerapkan konsep 3N ini, diharapkan peserta didik dapat melaksanakan pembelajaran dengan maksimal yakni dengan mengamati obyek pembelajaran, kemudian menirukan apa yang telah peserta didik amati, dan tahap terakhir peserta didik dapat menyempurnakan dengan menambahi obyek pembelajaran tersebut, sehingga dalam proses pembelajaran peserta didik akan menghasilkan pengetahuan dan keterampilan.Kata kunci:  Implementasi, Ajaran Ketamansiswaan Tri-N, budi pekerti luhur.